(untitled) (The Chittagong University Journal of Science, 2021)
This research paper is a modest attempt to examine the prevalence and differentials of drug addiction in slum and non-slum areas of Chittagong, Bangladesh. The study revealed that about 53 per cent of males and 47 per cent of females were drug addicted in slum areas while in non-slum areas, the percentages of the addicted males and females are about 73 and 55 respectively. In both the areas, it was observed that the drug addicted peoples were suffering from dyspepsia, pain in lever, declining sexual ability, hepatitis, vomiting and other diseases. From the multivariate analysis, it was observed that respondent’s religion, type of family, number of family members, economic status, occupation, duration of taking drugs, watching TV/LCD, reading newspaper or magazine, habit of smoking, knowledge about drugs, knowledge about the harmful effect of drugs, causes behind taking the drugs and drugs buying spots were found to be positively significant effect on drug addiction in slum areas, while in non-slum areas, respondent’s religion, educational qualifications, number of family members, economic status, occupation, knowledge about drugs, watching TV/LCD, reading newspaper or magazine, suffering from diseases due to drugs, knowledge about the harmful effect of drugs, type of drugs, causes behind taking drugs, drugs buying spots and tendency to come back from drugs were found to be positively significant effect on drug addiction. It was observed that majority of the addicted respondents use cannabis in both the areas compare to other type of drugs. The Chittagong Univ. J. Sci. 40(1) : 21-38, 2019